Wildlife management and conservation in South Africa: informing legislative reform through expert consultation using the Policy Delphi methodology - Mercugliano, Elena; Boshoff, Magdel; Dissegna, Arianna; Cerizza, Adriana F.; Laner, Luca; Indovina, Avery E.; Biasetti, Pierfrancesco; Da Re, Riccardo; Mascarello, Giulia; de Mori, Barbara (Frontiers in Veterinary Science, 2025)
South Africa’s wildlife sustainable management requires cohesive, evidence-based policy development that balances conservation goals with socio-economic needs. This study employed the Policy Delphi methodology, based on subsequent questionnaire rounds, to gather expert insights on critical priorities for wildlife-related policy, focusing on four species: lions (Panthera leo), elephants (Loxodonta africana), rhinos (Diceros bicornis and Ceratotherium simum), and leopards (Panthera pardus pardus). Experts were divided into panels based on species and areas of expertise: hunting, management, translocation, research, and animal welfare. Through three rounds, which took place from March to July 2024, the study sought to pinpoint South African policy issues needing amendment, addition, or removal, gathering expert opinions to achieve 70% consensus and suggestions for integrating these into policies. A total of 60 experts accepted to participate, 14 compiled all three Delphi questionnaires, while 40 of them contributed to at least one round. In Round 1, 34 experts suggested 523 pertinent issues meeting the study criteria: 260 amendments, 233 additions, and 30 removals. In Round 2, 28 participants considered 363 issues relevant, of which 254 obtained final agreement in Round 3 by 19 experts, divided into 19 thematic categories. Moreover, in Round 3, 617 suggestions for integration into policies were collected. Overall, the analysis underscores that the experts preferred modifying existing policies rather than removing measures, emphasizing the adequacy of the policies with adjustments. The final list of issues confirmed at the end of Round 3 and their categories represent experts’ priorities for the four focus species management reforms in South Africa. Moreover, the insights highlight gaps in South African wildlife legislation, including improved definitions, consideration of local communities, and addressing data deficiencies for evidence-based management and conservation. By identifying key areas for legislative improvement, this study provides a framework for actionable strategies to enhance wildlife policy in South Africa, following the broader aim of protecting wildlife, and with the potential of having an impact beyond national boundaries.